Pulpectomy with CTZ paste in a patient with sickle cell disease. Case report - Rivera-Salinas, Paulina (2024)
The aim of this clinical report case was to perform non-instrumental pulp therapy with CTZ in temporary dental organs in a patient with sickle cell disease (SCD). Female 5 years 7 months old, diagnosed with SCD was treated at Regional Hospital of High Speciality of the Child “Dr. Rodolfo Nieto Padrón” in the pediatric dentistry area. At the clinical observation presented tendons and conjunctival palidity, at the intraoral level presented mucous pallidity, hypomineralization, caries in various dental organs (DO), the results of blood biometry were a hemoglobin: 6.04 g/dl, erythrocytes: 1.82 g/ dl, leukocytes : 15 450 x 103/µL. Dental diagnosis was early childhood caries and pulpar necrosis in temporary molars 64 and 85 the first with dentoalveolar abscess. Non-instrumental pulp therapy treatment was carried out with CTZ in both temporary molars with pulp necrosis and as temporary glass ionomer restoration and subsequently steel crowns, temporary obturations in different DO for caries lesions. Result of CTZ treatment was effective, showing clinical and radiographic improvements. Non-instrumental pulp therapy with CTZ is a viable, fast and safe effective treatment in patients with SCD, prevents bacterial spread to periodontal tissues and minimizes systemic risk.